Testament of youth [videorecording (DVD)] - Harington, Kit, 1986-; Vikander, Alicia, 1988-; Egerton, Taron, 1989-; Morgan, Colin, 1986-; Brittain, Vera, 1893-1970 (Sony Pictures Home Entertainment, 2015)
A powerful story of love, war and remembrance, based on the First World War memoir by Vera Brittain, which has become the classic testimony of that war from a woman's point of view. A searing journey from youthful hopes and dreams to the edge of despair and back again, a film about young love, the futility of war and how to make sense of the darkest times.